2017
DOI: 10.1186/s12944-017-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat mass: is it the link between uric acid and diabetes risk?

Abstract: BackgroundUric acid (UA) has been suggested as a novel risk factor for diabetes. However, its definite role in this prevalent disease is still the subject of much discussion because it is always accompanied with other major risk factors such as obesity and high visceral adiposity. In order to clarify the role of UA in diabetes, this study aimed to investigate the associations between plasma UA and fasting plasma glucose, HbA1c, lipid profile and inflammatory markers after accounting for the contribution of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Further, the levels of pantothenic acid and uric acid were lower in the BET+PDX group, as in the HF control group, in SAT. Interestingly, in obese nondiabetics, the amount of VAT, but not SAT, correlated with serum uric acid levels . Hyperuricemia is associated with components of MetS, and uric acid has also been suggested as a novel risk factor for diabetes .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, the levels of pantothenic acid and uric acid were lower in the BET+PDX group, as in the HF control group, in SAT. Interestingly, in obese nondiabetics, the amount of VAT, but not SAT, correlated with serum uric acid levels . Hyperuricemia is associated with components of MetS, and uric acid has also been suggested as a novel risk factor for diabetes .…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in obese nondiabetics, the amount of VAT, but not SAT, correlated with serum uric acid levels. [38] Hyperuricemia is associated with components of MetS, and uric acid has also been suggested as a novel risk factor for diabetes. [38] The effect of BET on lipid species was nearly insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the risks for health are related to where body fat is stored. A higher level of android fat and/or its proportion in relation to gynoid fat, for instance, is linked to risk factors for developing diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sun et al (Sun et al 2015) found that uric acid-associated genes have an impact on insulin secrction in a Chinese patients with T2DM. Finally, another study (Seyed-Sadjadi et al 2017) showed that the associations between SUA and diabetes risk factors are Manuscript to be reviewed…”
Section: Discussionmentioning
confidence: 99%